Why are maternally separated females inflexible? Brain activity pattern of COx and c-Fos - Banqueri, María; Méndez, Marta; Arias, Jorge L. (Neurobiology of learning and memory, 2018)
•Brain changes in two length models of maternal separation are compared in females.•Spatial learning and flexibility are assessed in the Morris Water Maze.•Maternally separated females show different degree of impairment in flexibility.•Maternally separated females exhibit lower expression of c-Fos in prefrontal cortex.•Maternal separation alters brain energy metabolic networks in the two models. Subjects’ early life events will affect them later in life. When these events are stressful, such as child abuse in humans or repeated maternal separation in rodents, subjects can show some behavioral and brain alterations. This study used young adult female Wistar rats that were maternally raised (AFR), maternally separated from post-natal day (PND) 1 to PND10 (MS10), or maternally separated from PND1 to PND21 (MS21), in order to assess the effects of maternal separation (MS) on spatial learning and memory, as well as cognitive flexibility, using the Morris Water Maze (MWM). We performed quantitative cytochrome oxidase (COx) histochemistry on selected brain areas in order to identify whether maternal separation affects brain energy metabolism. We also performed c-Fos immunohistochemistry on the medial prefrontal cortex (mPFC), thalamus, and hippocampus to explore whether this immediate early gene activity was altered in stressed subjects. We obtained a similar spatial learning pattern in maternally raised and maternally separated subjects on the reference memory task, but only the controls were flexible enough to solve the reversal learning successfully. Separated groups showed less c-Fos activity in the mPFC and less complex neural networks on COx.